Policy-Relevant Attitudes Toward COVID-19 Vaccination: Associations With Demography, Health Risk, and Social and Political Factors - Katharina T. Paul; Jakob-Moritz Eberl; Julia Partheymüller (Frontiers Media S.A., 2021)
Background: Vaccination is considered to be a key public health intervention to end the COVID-19 pandemic. Yet, the success of the intervention is contingent on attitudes toward vaccination and the design of vaccination policies.Methods: We conduct cross-sectional analyses of policy-relevant attitudes toward COVID-19 vaccination using survey data of a representative sample of Austrian residents collected by the Austrian Corona Panel Project (ACPP). As outcomes, we examine the individual readiness to get vaccinated, the support for compulsory vaccinations, and the preference for making the vaccine available free of charge. The independent variables include demographics, objective and perceived health risks, and social and political factors.Results: Although there is broad public support for making the vaccine available free of charge, vaccine hesitancy and the opposition to a vaccine mandate are widespread. The protective function of the vaccine for the individual only motivates limited support for vaccinations. Opposition to COVID-19 vaccination also stems from a lack of sense of community and an ongoing politicization of the issue through conspiracy theories and party politics.Conclusion: We propose that overcoming the inherent free-rider problem of achieving sufficiently high vaccination rates poses a potential dilemma for policymakers: Given the politicized nature of the issue, they may find themselves having to choose between making vaccinations compulsory at political costs and a lingering pandemic at high costs for public health and the economy. We propose that promoting a sense of community and addressing potential practical constraints will be key in designing an effective COVID-19 vaccination policy.